2007
DOI: 10.1016/j.neuroimage.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of post mortem multiple sclerosis brain

Abstract: Magnetic resonance imaging (MRI) is being used to probe the central nervous system (CNS) of patients with multiple sclerosis (MS), a chronic demyelinating disease. Conventional T2-weighted MRI (cMRI) largely fails to predict the degree of patients' disability. This shortcoming may be due to poor specificity of cMRI for clinically relevant pathology. Diffusion tensor imaging (DTI) has shown promise to be more specific for MS pathology. In this study we investigated the association between histological indices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
268
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(294 citation statements)
references
References 58 publications
20
268
2
4
Order By: Relevance
“…They concluded that both techniques are sufficiently suited to detect microstructural tissue alterations at least in the white matter of the murine brain. Postmortem histological analyses assessing myelin content, axonal density, and gliosis revealed similar correlations in brains of patients with Alzheimer's disease [29] or multiple sclerosis [71][72][73].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 71%
“…They concluded that both techniques are sufficiently suited to detect microstructural tissue alterations at least in the white matter of the murine brain. Postmortem histological analyses assessing myelin content, axonal density, and gliosis revealed similar correlations in brains of patients with Alzheimer's disease [29] or multiple sclerosis [71][72][73].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 71%
“…The correlations between the diffusion tensor and histological parameters of human white matter had hitherto only been addressed in the postmortem state. In multiple sclerosis, DTI was demonstrated to correlate with axon counts and myelin (Schmierer et al, 2007(Schmierer et al, , 2008. Recently, it has been shown that postmortem diffusion anisotropy correlates with myelin basic protein in the developing human cerebellum of freshly aborted human fetuses (Saksena et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between DTI and myelin content and to a lesser extent axon count have been shown in humans, but were based on DTI acquired on postmortem brains of patients with multiple sclerosis (Schmierer et al, 2007). While brains are rapidly fixed in animal studies, this process is typically delayed in human cadavers.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis is a central nervous system disease characterized by a complex pathophysiology,1 the fundamental features of which have been derived from the analysis of post mortem tissue 2, 3, 4, 5. Spinal cord pathology is an important determinant of permanent neurological disability with cardinal characteristics being inflammatory demyelination, synaptic, neuronal and axonal loss 6, 7, 8, 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%